Process evaluation of a school-based sexual health intervention targeting 13–14-year-olds in Finland - Hanna Putkonen; Jari Kylmä; Tiina Rissanen; Marjorita Sormunen (Health Education, 2026)
Purpose A systematic approach to conducting process evaluations is essential for understanding the implementation of health interventions and their mechanisms of impact. This study aims to describe the process evaluation of a school-based, social-marketing-principles-utilising sexual health intervention targeting adolescents aged 13–14 in Finland. The content and delivery methods of the intervention, along with adolescents' engagement, learning, and functionality, were evaluated. Design/methodology/approach The Medical Research Council (MRC) framework for evaluation was utilised. Data were collected from adolescent questionnaires (n = 252) and teacher interviews (n = 6). Direct feedback, the researcher's observations, and relevant statistics were also gathered. Quantitative data were analysed using descriptive statistics, while qualitative data were examined using inductive content analysis. Findings The results indicated that the intervention was implemented consistently. Adolescents' satisfaction was predominantly good or very good. Nearly 60% of adolescents reported feeling engaged during intervention visits, and approximately one-third reported gaining new insights about sexuality. Adolescents particularly valued their active participation and opportunities for sexual communication, expressing a desire to learn more about sexual activity, dating, expressing sexual emotions, and sexual diversity. Teachers regarded the components of sexual communication and emotions as the most successful aspects of the intervention. Originality/value Process evaluations in adolescent sexual health promotion remain scarce. This study contributes to the knowledge base by demonstrating the value of systematic, theory-based evaluation in sexual health interventions and by providing insights drawn from real-world experiences in developing, implementing, and evaluating such interventions.